Supporting Risk Assessment Through a Visual, Browser-Based Tool...36th Medical Informatics Europe (MIE) Conference, May 25-28, 2026, Genoa, Italy. - GUNDLER, Christopher; ÜCKERT, Frank (Studies in Health Technology & Informatics, 2026)
Effective risk management in medical information systems calls for adherence to demanding international standards, including those for risk management and data protection. Translating these standards into daily interdisciplinary practice is often challenging due to the lack of intuitive and accessible tools that seamlessly connect regulatory frameworks with operational workflows. This study presents the design, implementation, and expert evaluation of a browser-based tool for visual risk modeling and assessment, specifically developed for application in medical informatics. The development was led by the Design Science Research framework, conducted in three phases: requirements and design, implementation, and, in the third step, evaluation. The developed application enables users to model processes with a simplified process notation, import and manage externally sourced hazard lists, and perform structured severity and likelihood assessments at each process step. For evaluation, four medical informatics experts utilized the tool to complete typical risk assessment tasks and subsequently assessed usability with the System Usability Scale. The ratings (83.75) highlight the tool’s intuitive interface and effective support for process-oriented risk assessment. These preliminary results indicate that browser-based, interactive tools can facilitate more systematic and collaborative risk management in medical informatics settings.